The Role of Glutathione in Male Infertility - Saeed Alkumait, Mohanned Hussam Mohammed (Eastern Journal of Medical Sciences, 2019)
Background: Numerous research studies have attempted to determine the causes of male infertility with the objective of developing therapeutic approaches to effectively improve various semen parameters. Aim: The presented intervention is a quantitative approach that categorically assesses the therapeutic advantage of oral GSH (glutathione) administration on various semen parameters including sperm concentration, morphology, and motility in infertile males. Methods: The prospective placebo-controlled study included 101 infertile adult males through random selection between the timeframe of Jan 2017 to Mar 2018. We selected total 101 subjects who did not experience any chronic disease of the reproductive system and exhibited normal female factor. GSH oral therapy was administered between 0 to 6 months, 51 patients received GSH therapy and 50 patients received placebo in the form of glucose sachets. At the time of 0, 3 and 6 months, the blood and semen samples were taken for analyses for treatment and placebo groups. Results: The findings recorded at 0 weeks, 3 months, and 6 months interval revealed a significant p-value. At 0 week, there wasn’t any  statistical significance for the results while at 3 months, GSH value was 4.55 mg/dl for GSH group therapy in comparison for 1.55 mg/dl for placebo group which was statistically significant. Conclusion: The study findings revealed a strong positive relationship between oral GSH therapy and the selected sperm parameters.